Kinetics of reductive alkylation of p-phenylenediamine with methyl ethyl ketone using 3% Pt/Al2O3 catalyst in a slurry reactor - Patil, Narendra G.; Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Intrinsic kinetics of reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) using 3% Pt/Al2O3 catalyst was studied in a slurry reactor. The overall reaction involves a combination of parallel and consecutive reactions involving equilibrium noncatalytic (homogeneous) and catalytic (heterogeneous) steps. For the purpose of kinetic modeling, the effects of PPDA concentration, catalyst loading, agitation speed, and partial pressure of hydrogen were studied in a temperature range of 373-413 K. Quantitative criteria were used to ensure that the reaction occurred in the kinetic regime. Different rate equations have been considered based on the elementary steps involving catalytic and noncatalytic reactions, which lay stress on the different types of interactions occurring between the reactants and the active catalyst sites. The best-fit rate model has been proposed by rigorous optimization and model discrimination procedures, by simulating the experimental concentration-time data. For the best-fit model, the agreement between the predicted and experimental data was found to be very good over a wide range of operating conditions.